Is humanistic education possible? - Willnatis, Arnoldas (Socialinė teorija, empirija, politika ir praktika, 2003)
The conception of humanistic education is presented in the paper. The concepts of humanity and education are presented in the first part. The analytical lenses are presented in the second part. The phenomena is analysed in the philosophical, ethical and practical dimensions. It is shown that the concept of humanistic education is related to organisation. Any organisation can be viewed through the lenses of humanistic education. And it is possible to evaluate certain organisation in the perspective of humanistic education. The author argues, that educational organisations must seek to become humanistic and the strategy for the transformation into the humanistic educational organisation is presented.
Keywords: Education; Humanistic; Education organisation